In situ Tribo-Fluorination for Oil-Less Hermetic Compressor Applications - Borges, Gabriel; Salvaro, Diego; Binder, Roberto; Binder, Cristiano; Klein, Aloisio N.; de Mello, Jose D. B. (Frontiers in Mechanical Engineering, 2021)
In the present work, we overview the multidisciplinary development of a regular, lubricated, hermetic compressor which works in an on-off cycle, circular motion, single-speed, many tribological contacts, into an innovative, linear motion, variable displacement, single tribological contact, oil-less hermetic compressor presenting high versatility in terms of refrigerator design, sustainability and improved efficiency. The original approach encompassed the development of new surface engineering procedures applying purpose-oriented phases to soft substrates. Particular emphasis is given to the in situ fluorination of the tribolayer formed in the piston-cylinder tribopair. Although chlorinated halocarbons (CFC) are efficient refrigerants from a thermodynamic point of view, they do have serious environmental implications that have forced the refrigeration industry to switch to more environmentally friendly hydrofluorocarbon (HFC) based refrigerants. The first and most successful alternative to the CFCs was tetrafluorocarbon, particularly tetrafluoroethane (CF3CH2F), aka R134a refrigerant. The current trend to downsizing mechanical systems, smaller clearances, and increased speeds leading to greater energy efficiencies associated with miscibility issues imposing the use of costly, fully synthetic lubricants with the R134a refrigerant gas led to the introduction of a new hermetic compressor design, the Wisemotion®, the first, and until now, unique, oil-free hermetic compressor on the world market. In this context different types of multi-layers, their thickness, substrate material, processing routes, etc., have been studied and optimized. Si-rich hydrogenated DLC (a:C-H) presented enhanced tribological properties when tested under fluorine-rich atmospheres, and semi-industrial scale tests have been carried out to understand this point further. A homemade tribological emulator was developed allowing close-to-real tribopair, atmosphere, and imposed mechanical conditions used in an oil-free commercial hermetic compressor. The tests were carried under different stroke frequencies (5, 20, and 40 Hz) and atmospheres (R134a, ambient air, and argon). Results showed a strong influence of both atmosphere and stroke frequencies. The friction coefficients were significantly lower (~3.8X) for the refrigerant gas atmosphere, attributed to the fluorine and highly disordered graphitic structures rich tribolayers. Under the high frequency (40 Hz), the energy input seems to be a deterrent to the formation of stable tribolayers, and the DLC coating shatters on the first few sliding meters.